CALCULATION OF THE AUDIENCE OF THE RADIAL TYPE OF AUDIENCE IN THE PROCESS OF LEARNING WITH THE HELP OF ERGONOMICS - Khaldarov Kh. A.; Primkulova Alima Asetovna; Karimova Madina Khodjiakbarovna (Scholar Express Journal, 2022)
This article is devoted to the study of the soundness of the audience of the radial type in the quality management of the learning process in the acquisition of knowledge trained in education. As well as determining the coefficient of the degree of sounding by the levels of location of trainees in the audience.
Keywords: Voiced sound; ergonomics; ergonomic model; mathematical model